Antifungal Activities of Bacillus subtilis Lipopeptides to Two Venturia inaequalis Strains Possessing Different Tebuconazole Sensitivity - Desmyttere, Hélène; Deweer, Caroline; Muchembled, Jérôme; Sahmer, Karin; Jacquin, Justine; Coutte, François; Jacques, Philippe (Frontiers in Microbiology, 2019)
Within the framework of biocontrol development, three natural substances produced by Bacillus subtilis, called lipopeptides, have been studied: fengycin (F), surfactin (S) and mycosubtilin (M). Their antifungal properties were tested in vitro, in liquid medium, on two strains of Venturia inaequalis, ascomycete fungi causing apple scab. These two strains were respectively sensitive and less sensitive to tebuconazole, an active substance of the triazole family. These three molecules were tested on their own, in binary (FS, FM, SM) and ternary mixtures (FSM). The antifungal activities of lipopeptides were estimated by calculating an IC50, compared to tebuconazole chemical substance. In tests involving the sensitive strain, all lipopeptide modalities exhibited antifungal activity. However, modalities involving fengycin and its mixtures exhibited the best antifungal activities; the activity of fengycin alone being very similar to that of tebuconazole. Interestingly, regarding the strain with reduced sensitivity to tebuconazole, surfactin and fengycin alone were not efficient while mycosubtilin and the different mixtures showed interesting antifungal activities. Specifically, the antifungal activity of FS and FSM mixture were equivalent to that of tebuconazole. For both fungal strains, microscopic observations revealed important morphological modifications in the presence of fengycin and in a less important proportion in the presence of surfactin but not in the presence of mycosubtilin. Overall, this study highlights the diversity in mode of action of lipopeptides on apple scab strains.